2015
DOI: 10.1159/000376548
|View full text |Cite
|
Sign up to set email alerts
|

Elastin Organization in Pig and Cardiovascular Disease Patients' Pericardial Resistance Arteries

Abstract: Peripheral vascular resistance is increased in essential hypertension. This involves structural changes of resistance arteries and stiffening of the arterial wall, including remodeling of the extracellular matrix. We hypothesized that biopsies of the human parietal pericardium, obtained during coronary artery bypass grafting or cardiac valve replacement surgeries, can serve as a source of resistance arteries for structural research in cardiovascular disease patients. We applied two-photon excitation fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 52 publications
2
26
1
Order By: Relevance
“…The structure of the small arteries employed in these studies using nonlinear microscopy was consistent with that observed in fixed human pericardial resistance arteries (6), with the exception that in this study no fibrous collagen was observed in the media. The structure of the two fibrous networks in the adventitia was similar to that seen in both large (10, 50) and small (6) arteries. It was notable that none of the vessels contained the fenestrated sheets of elastin reported in the intima of resistance arteries in other studies (11).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The structure of the small arteries employed in these studies using nonlinear microscopy was consistent with that observed in fixed human pericardial resistance arteries (6), with the exception that in this study no fibrous collagen was observed in the media. The structure of the two fibrous networks in the adventitia was similar to that seen in both large (10, 50) and small (6) arteries. It was notable that none of the vessels contained the fenestrated sheets of elastin reported in the intima of resistance arteries in other studies (11).…”
Section: Discussionsupporting
confidence: 81%
“…In the IEL the fibers were predominantly axially aligned at low pressure but at higher pressure spread apart to reveal gaps bridged by regularly spaced bracing fibers, which appear on the orientation plot as an emerging peak around 0°. This honeycomb-like structure has been visualized at much higher pressures (6) and its mechanical properties analyzed in large arteries (10). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used this indirect approach because mechanical removal and selective chemical damage of the endothelium proved to be difficult and poorly reproducible in human pericardial resistance arteries. This contrasts with experimental animal resistance arteries that we investigated previously and may be related to the unusual structure of the internal elastic lamina in the pericardial resistance arteries [22]. For a few patients, arterial segments did not contract in response to all three contractile stimuli, but only to two of K + , ET-1 and U46619.…”
Section: Methodscontrasting
confidence: 84%
“…Selective removal of the endothelium by mechanical or chemical methods without damage to the smooth muscle proved to be difficult and poorly reproducible in these human pericardial resistance arteries. The unusual structure of the internal elastic lamina [22] and the small contractility of the smooth muscle in these vessels (maximal contractility: approximately 1.5 N/m versus 5.0 and 10.0 N/m in rat mesenteric and pig pericardial resistance arteries, respectively [11,22]) may have contributed. Instead, we used pharmacological inhibitors of several established mechanisms of EDR, such as COX, NOS, K Ca 2.3 and K Ca 3.1.…”
Section: Discussionmentioning
confidence: 99%